New species of Ceropegia (Apocynaceae) from the Horn of Africa - Bruyns, Peter V.; Klak, Cornelia; Mazuch, Tomáš; Gelle, Faysal Jama; Elmi, Hassan Sh Abdirahman; Hanáček, Pavel (Phytotaxa, 2020)
We describe three new species of Ceropegia L., namely C. buraoensis Bruyns of sect. Echidnopsis (Hook.f.) Bruyns from Somaliland, C. marronina Bruyns & Hanáček of sect. Orbea (Haw.) Bruyns from northern Ethiopia and C. pseudorhynchantha Bruyns of sect. Phalaena H.Huber from southern Ethiopia.